2024
DOI: 10.3390/su16052001
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Integrated Design Approach for Life Cycle Zero-Carbon Buildings

Ehsan Kamel,
Francesco Pittau,
Laura Mora Dal Verme
et al.

Abstract: Implementing net-zero carbon design is a crucial step towards decarbonizing the built environment during the entire life cycle of a building, encompassing both embodied and operational carbon. This paper presents a novel computational approach to designing life cycle zero-carbon buildings (LC-ZCBs), utilizing parametric integrated modeling through the versatile Grasshopper platform. A residential building located at the New York Institute of Technology, optimized to fulfill the LC-ZCB target, serves as a case … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Kamel et al [36] demonstrated the feasibility of using parametric modeling with Grasshopper to design nZCBs. The research identified key parameters including geometry, construction technology, envelope thermal resistance, and on-site renewable energy production.…”
Section: Analytical and Parametric Modelingmentioning
confidence: 99%
“…On the other hand, Kamel et al [36] demonstrated the feasibility of using parametric modeling with Grasshopper to design nZCBs. The research identified key parameters including geometry, construction technology, envelope thermal resistance, and on-site renewable energy production.…”
Section: Analytical and Parametric Modelingmentioning
confidence: 99%